Les embûches du courtage d’assurance - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1992)
One of the most significant legal developments of recent times involving insurance brokers is the emergence of the notion of duty to give expert advice. In this article, the author uses practical examples to illustrate how brokers are increasingly found to be at fault and are condemned by courts when they fail to exercise reasonable care as professional advisors to their clients, in preparing or completing application forms, in giving advice on insurance matters or by failing to provide such advice.